Strategi Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kompetensi Pedagogik Guru di SMA Negeri 2 Bone - Ansar, Ahlun; Arismunandar; Wahira (Universitas Kristen Satya Wacana, 2023)
In light of concerns about low teacher competence in Indonesia, this study investigates the leadership strategies employed by the principal of SMAN 2 Bone to improve the pedagogic competence of teachers. The objective of the study is to discover the principal's leadership strategy in improving the teachers competence at SMAN 2 Bone. This type of research is qualitative with a descriptive approach. Data collection conducted by interview, observation, and documentation. The results of the study reveal that the principal's leadership strategy in improving pedagogic competence of teachers are: 1) providing opportunities and facilities for teachers in various education and training such as PPG, Education and Training, MGMP, Workshops, Seminars, and other programs that can support teacher pedagogical competence improvement; 2) conducting teaching supervision to teachers on learning management and providing post-conference or evaluation guidance after supervising; 3) conducting In-house Training program; 4) enhancing teacher discipline by controlling teacher attendance such as punctuality in school attendance, teaching time, and providing exemplary attitudes to teachers; and 5) involving teachers in various teacher professional organizations.